IDENTIFIKASI RUMAH TANGGA RAWAN BENCANA GEMPA BUMI DI WILAYAH KABUPATEN BANTUL-DI YOGYAKARTA - Nurhadi Nurhadi (Jurnal Sosiologi Reflektif, 2015)
Depending on the condition of vulnerability, disasters bring about different consequences to different households. Using the Sustainable Livelihood (SLA) framework, the research carried out in the earthquake-prone area of Bantul-Yogyakarta results in three conclusions. First, the wealthiest suffer the least because of their capabilities of reducing the impact of earthquake disaster by fortifying their houses and by improving their livelihood assets. Second, despite their sufferings, the poor tend to be more able to reduce the impact of future disaster event to their livelihoods, thanks to the strong social capital which had minimized the cost of housing reconstruction. Third, it is the self-suffiient group which is most prone to the disaster event. This is due their wealth had been eroded by overwhelming cost of house reconstruction and their inabilities to reduce labor cost.